(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about the patriotic factors of attracting young people to the military field in military educational institutions. The purpose of the article is to create a sense of patriotism among citizens, to involve them in strengthening the country’s defense capabilities, and to develop military skills necessary for the defense of the homeland.